Comparison of adenosine-independent pressure indices to fractional flow reserve in stent-jailed bifurcation side branches - Altstidl, Johannes Michael; Achenbach, Stephan; Marwan, Mohamed; Tröbs, Monique; Schacher, Nora; Ferstl, Paul; Gerlach, Andreas; Schlundt, Christian; Gaede, Luise (Catheterization and Cardiovascular Interventions, 2022)
Objectives and Background: This study aims to evaluate whether the high correlation and classification agreement of the instantaneous wave-free ratio (iFR) and the resting distal coronary to aortic pressure ratio (Pd/Pa) with the fractional flow reserve (FFR) can be confirmed in stent-jailed side branches (J-SB). Methods: Consecutive patients (n = 49) undergoing provisional stenting were prospectively enrolled and a physiological assessment of the J-SB (n = 51) was performed. FFR, iFR, and Pd/Pa were measured and the hemodynamic relevance was determined using cutoff values of ≤0.80, ≤0.89, and ≤0.92, respectively. Results: Both iFR (r = 0.75) and Pd/Pa (r = 0.77) correlated closely with FFR. Classification agreement with FFR was 78% for iFR (81% sensitivity, 77% specificity) and 75% for Pd/Pa (63% sensitivity and 80% specificity). However, angiographic diameter stenosis and pressure indices correlated poorly. For a threshold of ≥70% stenosis, agreement concerning hemodynamic relevance was found in 59% for FFR, 69% for iFR, and 61% for Pd/Pa. Conclusion: As reported for other lesion types, FFR and the adenosine-independent pressure indices iFR and Pd/Pa show close correlation and a high classification agreement of approximately 75%–80% in J-SB. Therefore, iFR can be regarded as a recommendable alternative to FFR for the guidance of provisional stenting in bifurcation lesions.
CRIS-Team Scopus Importer:2022-07-01
Keywords: catheterization diagnostic; coronary artery disease; fractional flow reserve

Double kissing - crush technique to treat coronary bifurcation lesions: analysis of success rate, procedural times and device usage - Schacher, Nora; Ferstl, Paul; Weidinger, Franz; Achenbach, Stephan; Tröbs, Monique; Marwan, Mohamed; Gaede, Luise (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Impact of COVID-19 lockdown on the procedural and intra-hospital outcome of STEMI patients - Gaede, Luise; Rittger, H.; Gerrens, H.; Achajew, A.; Schacher, Nora; Ferstl, Paul; Tröbs, Monique; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Impact of single nucleotide polymorphisms in the VEGFR2 gene on endothelial cell activation under non‑uniform shear stress - Schacher, Nora; Raaz-Schrauder, Dorette; Pasutto, Francesca; Stumpfe, Florian M.; Tauchi, Miyuki; Dietel, Barbara; Achenbach, Stephan; Urschel, Katharina (International Journal of Molecular Medicine, 2019)
Single nucleotide polymorphisms (SNPs) in vascular endothelial growth factor receptor 2 (VEGFR2) are associated with coronary artery disease, hypertension and myocardial infarction. However, their association with atherosclerosis remains to be fully elucidated. The purpose of the present study was to determine whether SNPs are involved in atherogenesis, by analyzing their impact on human umbilical vein endothelial cells (HUVECs) under laminar and non-uniform shear stress in a well-established in vitro model that simulates shear stress-induced proatherogenic processes at vessel bifurcations. All experiments were performed using freshly isolated HUVECs. Three SNPs in the VEGFR2 gene (rs1870377 T>A, rs2071559 A>G and rs2305948 C>T) were genotyped and the expression levels of VEGFR2 were semi-quantitatively determined using western blotting. Subsequently, the HUVECs were seeded in bifurcating flow‑through cell culture slides and flow (9.6 ml/min) was applied for 19 h, including tumor necrosis factor-α stimulation during the final 2 h of flow. The protein expression levels of VCAM-1, E-selectin and VEGFR2 and the adhesion of THP-1 cells were analyzed in laminar and non-uniform shear stress regions. Data were analyzed for associations with the respective SNPs. The total expression of VEGFR2 was significantly lower under non‑uniform shear stress than under laminar shear stress conditions, independent of the genotype. The expression of VEGFR2 between the different shear stress patterns was not significantly altered by the different SNPs. The expression levels of VCAM-1 and E-selectin were lower in the A/A genotype compared with those in other genotypes in rs1870377 T>A and rs2071559 A>G. In conclusion, the results suggested that SNPs within the VEGFR2 gene have a significant impact on shear stress‑related endothelial activation.
CRIS-Team Scopus Importer:2019-08-30
Keywords: Adhesion molecules; Atherosclerosis; Endothelial dysfunction; Shear stress; Single nucleotide polymorphism; Vascular endothelial growth factor receptor 2

IMPACT OF SINGLE NUCLEOTIDE POLYMORPHISMS RS1870377 A > T AND RS2305948 C > T ON ENDOTHELIAL CELL ACTIVATION UNDER NON-UNIFORM SHEAR STRESS - Urschel, Katharina; Schacher, Nora; Pasutto, Francesca; Achenbach, Stephan; Raaz-Schrauder, Dorette; Schrauder, Michael G.; Stumpfe, Florian; Dietel, Barbara (2017)
EVALuna2:9363

Outcome after new generation single-layer polytetrafluoroethylene-covered stent implantation for the treatment of coronary artery perforation - Kufner, Sebastian; Schacher, Nora; Ferenc, Miroslaw; Schlundt, Christian; Hoppmann, Petra; Abdel-Wahab, Mohamed; Mayer, Katharina; Fusaro, Massimiliano; Byrne, Robert A.; Kastrati, Adnan (Catheterization and Cardiovascular Interventions, 2019)
Aims: Coronary artery perforation (CAP) is a rare but severe complication during percutaneous coronary intervention (PCI). Implantation of covered stents (CS) represents a potentially life-saving treatment. Concerns exist regarding limited efficacy and high stent thrombosis (ST) rates related to early generation CS. The aim of this study was to evaluate angiographic and clinical outcomes of patients with CAP treated with a new generation single-layer polytetrafluoroethylene (PTFE)-CS. Methods: Between May 2013 and November 2017, we identified a total of 61 patients who underwent implantation of 71 single layer PTFE-CS after CAP. We analyzed angiographic results at follow up (including binary angiographic restenosis [BAR] and late-lumen-loss [LLL]) and clinical outcomes in hospital and at follow up, including target lesion revascularization (TLR), cardiovascular-, and all-cause mortality, myocardial infarction (MI) and stent thrombosis (ST). Results: Procedural success was achieved in all but two patients (96.7%). Procedure related MI, occurred in 19 cases (31.1%), in hospital death occurred in five cases (8.2%). At follow-up, TLR occurred in 11 cases (18.0%), two patients (3.3%) died from non-cardiovascular cause, there was no case of MI or ST. Conclusions: In this retrospective analysis, implantation of a new generation PTFE-CS, for the treatment of CAP showed high technical success rates. Although, periprocedural MI—and in-hospital-death rates remain not inconsiderable, new generation PTFE-CS showed favorable angiographic and clinical efficacy and high safety profile, especially with regard to thrombotic events.
CRIS-Team Scopus Importer:2019-05-02
Keywords: coronary artery perforation; covered stent

Radial versus femoral approach for rotational atherectomy - technical aspects and procedural outcomes - Bargon, Sophie; Achenbach, Stephan; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Ammon, Fabian; Ferstl, Paul; Schacher, Nora (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Rotational atherectomy via the transradial access: success rates, procedural parameters and complications - Ferstl, Paul; Drentwett, Anne-Sophie; Bargon, Sophie; Schacher, Nora; Tröbs, Monique; Marwan, Mohamed; Achenbach, Stephan; Gaede, Luise (Heart and Vessels, 2022)
Radial access is recommended for percutaneous coronary intervention (PCI), but rotational atherectomy remains frequently performed via femoral access. Analyzing the procedural parameters, success rate and complications of rotational atherectomy, performed via radial in comparison to femoral access. We retrospectively analyzed 427 consecutive patients undergoing rotational atherectomy. Procedural parameters and outcome were determined in 171 patients, scheduled for radial and compared to 256 patients with femoral access use. In the radial access group (74 ± 9 years, 84% male), the LAD was most frequently treated (49%). Sheath size was 7F in 59% and 6F in 41%, burr size was 1.5 mm in 46% and 1.25 mm in 14% of patients. A temporary pacemaker was inserted in 14%. Procedural success rate stood at 97%. Access site complications occurred in 4% of patients, which was significantly less frequent than in in 256 patients treated via femoral access (13% p = 0.003). Compared to radial access, femoral access was associated with the use of larger sheaths (p < 0.001), more frequent treatment of non-LAD vessels (58.2% vs. 44.4%, p = 0.013) and a higher rate of temporary pacemaker use (27%; p = 0.001). No differences could be seen in procedural success (p = 0.83) and burr size (p = 0.51). Femoral access (OR 3.33; 95% CI 1.40–7.93), and female sex (OR3.40 95% CI 1.69–6.63) were independent predictors for access site complications. For coronary rotational atherectomy, radial access has a high success rate with overall use of smaller sheaths, but of equally sized burrs as well as a significant lower rate of access site-related complications than femoral access.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Percutaneous coronary intervention; Radial access; Rotational atherectomy; Transradial